Susceptibility to hamstring injuries in soccer. A prospective study using muscle functional magnetic resonance imaging - Schuermans, J.; Van Tiggelen, D.; Danneels, L.; Witvrouw, E. (The American Journal of Sports Medicine, 2016)
Background: Running-related hamstring strain injuries remain a delicate issue in several sports such as soccer. Their unremittingly high incidence and recurrence rates indicate that the underlying risk has not yet been fully identified. Among other factors, the importance of neuromuscular coordination and the quality of interplay between the different hamstring muscle bellies is thought to be a key determinant within the intrinsic injury risk. Muscle functional magnetic resonance imaging (mfMRI) is one of the tools that has been proven to be valid for evaluating intermuscular coordination. Purpose: To investigate the risk of sustaining an index or recurring soccer-related hamstring injury by exploring metabolic muscle characteristics using mfMRI. Study Design: Cohort study; Level of evidence, 2. Methods: A total of 27 healthy male soccer players and 27 soccer players with a history of hamstring injuries underwent standardized mfMRI. The mfMRI protocol consisted of a resting scan, a strenuous bilateral eccentric hamstring exercise, and a postexercise scan. The exercise-related T2 change, or the signal intensity shift between both scans, was used to detect differences in metabolic characteristics between (1) the different hamstring muscle bellies and (2) the prospective cohorts based on the (re)occurrence of hamstring injuries during a follow-up period of 18 months. Results: The risk of sustaining a first hamstring injury was associated with alterations in the intermuscular hierarchy in terms of the magnitude of the metabolic response after a heavy eccentric effort, with the dominant role of the semitendinosus set aside for a higher contribution of the biceps femoris (P = .017). Receiver operating characteristic (ROC) curve analysis demonstrated that this variable was significantly able to predict the occurrence of index injuries with a sensitivity of 100% and a specificity of 70% when the metabolic activity of the biceps femoris exceeded 10%. The risk of sustaining a reinjury was associated with a substantial deficit in hamstring strength endurance (P = .031). Soccer players who sustained a reinjury were only able to perform prone leg curls for a mean duration of 146.50 ± 76.16 seconds, whereas those with an injury history but no recurrence during follow-up were able to continue for a mean of 237.45 ± 110.76 seconds (95% CI, 11.9-230.5 seconds; P = .031). Conclusion: This was the first study to assess the causal relation between the intramuscular recruitment pattern and the risk of sustaining an index or secondary hamstring strain. Changes in intermuscular interplay seem to significantly increase the risk of sustaining index hamstring injuries in male amateur soccer players. Inadequate eccentric muscle endurance could be associated with an increased risk of sustaining a recurring hamstring injury.